PROXIMATE COMPOSITION AND SENSORY QUALITIES OF FAT REDUCED CHEVON SALAMIS ENRICHED WITH DIETARY FIBER (Indian Journal of Animal Production and Management, 2013)
The proximate composition and sensory qualities of low fat chevon salamis prepared by incorporating 10% goat fat (GF) and three different levels of dietary fibers viz. wheat bran (WB) and oat bran (OB) added @2%, 3% fiber & 4% (T1, T2 & T3) respectively were evaluated in this study. WB and OB were added in such quantities that maintains equal proportion of dietary fiber in the product from either source. The control product contained 20 per cent GF with no added dietary fiber sources. The study revealed significant decrease in percent moisture, crude protein, ether extract and total ash contents along with the increased incorporation levels of dietary fibers in the treated formulations. Sensory evaluation chevon salamis showed significant decrease (P
Keywords: Proximate composition; chevon salamis; sensory qualities; low fat